KERUGIAN PELAKU USAHA AKIBAT RETURN BARANG OLEH KONSUMEN: Perbandingan antara Undang – Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen dengan Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik - Muhammad Tegar Pandu Prakoso; Anang Dony Irawan (Journal of Indonesian Comparative of Syari'ah Law, 2025)
This study analyzes the legal comparison between the Electronic Information and Transactions Law (UU ITE) and the Consumer Protection Law (UUPK) in regulating losses experienced by business actors due to the return of goods by consumers in e-commerce transactions, especially with the Cash on Delivery (COD) payment system. The research method used is normative. This study aims to identify legal loopholes in the UUPK and the ITE Law related to the protection of business actors, and to analyze how these two laws can be implemented simultaneously to provide balanced protection. The results of the study show that although the UUPK and the ITE Law provide legal guarantees for business actors, there are no regulations that specifically regulate the division of risk and responsibility in COD transactions. Therefore, a more comprehensive regulation is needed to protect business actors from potential losses due to the return of goods. This research is expected to contribute to the development of better policies in protecting business actors and creating safer and fairer e-commerce transactions for all parties involved.d into 3 namely medical assistance, psychological assistance, and legal assistance.